Implementasi Metode Drill dalam Pembelajaran Hukum Bacaan Nun Sukun dan Tanwin bagi Siswa Kelas IV - Nurtang, Nurtang (Madrasah Ibtidaiyah Research Journal, 2023)
The implementation of the drill method in learning the law of reading nun sukun and tanwin for fourth-grade students aims to find out the implementation of the drill method in learning the law of reading nun sukun and tanwin for class IV students of MI Syamsu Rasyidi Majang, Bone district. The author uses a qualitative research type. Data were collected through observation, interviews, tests, and documentation. Furthermore, the data were analyzed by reducing data, presenting data, and drawing conclusions or verification. The results showed that: First, the planning for the implementation of the drill method in learning the reading laws of nun sukun and tanwin for fourth-grade students had been carried out properly. This is evident before entering class the teacher already has a mature plan contained in the lesson plan that comes from the syllabus. Second, the implementation of the drill method in learning the reading law of nun sukun and tanwin for grade IV students has been well implemented. The teacher conveys material using media and games, repeating izhar halqi and ikhfa' haqiqi material several times until students understand the material correctly. Third, students' assessment of the implementation of the drill method in learning the reading laws of nun sukun and tanwin for grade IV students is that all students feel very happy and happy to be able to learn using the drill method so they can understand and memorize the material easily.